Pakistan occupied Kashmir the untold story - Gupta, Virendra 1954-.; Bansal, Alok.; Institute for Defence Studies and Analyses (New Delhi Manas Publications, 2007)
Contributed articles.
"Institute for Defence Studies and Analyses, New Delhi."
Keywords: Azad Kashmir -- Politics and government -- 20th century; Azad Kashmir -- Politics and government -- 21st century